Genetic structure and relationship of three cattle breeds from Rajasthan: Implications for breeding strategies and conservation - B. Prakash; Deepika (Journal of Livestock Biodiversity, 2025)
Information on genetic structure and variability of livestock breeds is critical for efficient conservation plans. Here, we present molecular characterization of 3 cattle breeds from Rajasthan state of India on the basis of 21 FAO recommended microsatellite markers. All the three breeds had high diversity values. The average number of alleles per locus was 9.00 in Tharparkar, 9.76 in Nagori and 10.33 in Kankrej. Gene diversity (expected heterozygosity) was high in all breeds and varied from 0.707 in Tharparkar, 0.713 in Nagori to 0.755 in Kankrej. FIS values were very low (almost zero) in all the three breeds, with mean FIS values ranging from -0.018 in Kankrej to -0.025 in Nagori. Phylogenetic analysis by Neighbour Joining tree based on Nei’s genetic distance and Cavalli-Sforza Edwards chord distances generated identical phylogenies, which are in accordance with historical and geographical data. Tharparkar and Kankrej clustered together while Nagori was distinct. AMOVA revealed very low breed differentiation among the three breeds. Only 2.19% variation was due to between breed differences and the remaining 97.81% was due to individuals within breeds. PCA and MDS analysis revealed mixed breed structure. A very high migration (average 11.26 immigrants per generation) was estimated between the three breeds. The study thus reveals very low genetic differentiation despite high genetic variability in the three investigated breeds.